Translation, reliability, agreement and validity of the Turkish version of Cumulated Ambulation Score in patients with hip fracture - KURU ÇOLAK, TUĞBA (TURKISH JOINT DISEASES FOUNDATION, 2020)
Objectives: This study aims to translate and investigate the inter-rater reliability, agreement and validity of the Turkish version of the Cumulated Ambulation Score (CAS-TR) in patients with hip fracture. Patients and methods: This study included patients with a hip fracture of the femoral neck between July 2019 and March 2020 at the Dr. Lutfi Kirdar Kartal Training and Education Hospital, Department of Orthopedics and Traumatology, Istanbul. The CAS manual and score-sheet were translated into Turkish. An orthopedician and a physiotherapist independently administered the CAS-TR to 36 patients (12 males, 24 females; mean age 78.7 years; range, 65 to 90 years) at postoperative days one, two, three and 30. Weighted Cohen's kappa coefficient was used to measure inter-rater reliability. Turkish version of modified Barthel Index was used for analysis of validity. Results: The majority of the patients had type III fracture (72.2%) according to Garden's classification. The kappa value was >= 0.90 for days one-three, the total and 30th day score of CAS-TR. The observed agreement ranged between 91.6% and 100% for all assessments. Validity analysis showed a significantly positive correlation between day two and day 30 CAS-TR and Barthel scores. Conclusion: We found almost perfect reliability, high percentage agreement and acceptable convergent validity of the CAS-TR. We recommend the CAS to be used as an easily applicable instrument to assess basic mobility status in Turkish patients with hip fracture. Orthopedic and geriatric patients and patients undergoing any type of surgery can be assessed with CAS for early evaluation of mobility status.
Keywords: Arthroplasty; femoral neck fracture; hip; mobility; BASIC MOBILITY; HOSPITAL DISCHARGE; MORTALITY; REHABILITATION; MORBIDITY